Partial vs Radical Nephrectomy for T1–T2 Renal Masses in the Elderly: Comparison of Complications, Renal Function, and Oncologic Outcomes - An, Julie Y. (Urology, 2016)
OBJECTIVE: To compare outcomes of partial nephrectomy (PN) and radical nephrectomy (RN) in patients 65 years and older. MATERIALS AND METHODS: Our institutional renal mass registry was queried for patients 65 and older with solitary cT1–T2 renal mass resected by PN or RN. Clinicopathologic features and perioperative outcomes were compared between groups. Renal function outcomes measured by change in estimated glomerular filtration rate (eGFR) and freedom from eGFR< 45 mL/min/1.73 m(2) were analyzed. Multivariate Cox proportional hazard models for overall survival and cancer-specific survival were analyzed. RESULTS: Overall, 787 patients met inclusion criteria. Of these, 437 (55.5%) underwent PN and 350 (44.5%) underwent RN. Median follow-up was 36 months. Patients in the PN cohort were younger (median age 70.3 years vs 71.9 years, P < .001), had lower American Society of Anesthesiologists scores (2.6 vs 2.8, P = .001), smaller tumors (tumor diameter 2.8 cm vs 5.0 cm, P < .001), and lower proportion of renal cell carcinoma (76.7% vs 87.4%, P < .001). Perioperative outcomes were similar between PN and RN groups as were complications (37.8% vs 38.9%). Estimated change in eGFR was less in PN vs RN (6.4 vs 19.7, P < .001) at last follow-up. Overall survival and cancer-specific survival were equivalent between modalities. CONCLUSION: Because the renal functional benefit of PN is realized over many years and the procedure has a higher historical complication rate than RN, some suspected elderly patients might benefit more from RN over PN. However, these data suggest that elderly patients are not harmed and may potentially benefit from PN. Age alone should not be a contraindication to nephron-sparing surgery.